Ex Africa semper aliquid novi? - Duncan, Graham (HTS teologiese studies, 2005)
Elizabeth Isichei follows in a grand tradition of single-author one-volume histories of Christianity in Africa. It is written in the current ecumenical tradition from “an African perspective” and follows the canons of the “new historiography”. In terms of periodisation and regional divisions, she follows generally accepted categories with some local variations. What is distinctive and innovative is the selectivity of some of the themes she chooses to discuss. In the absence of similar works emanating from black historians, she expresses her concern about being a “white” interpreter and interlocutor. Nevertheless, she offers a history of considerable distinction.